The Effect of Organic and Conventional Farming on Land Quality and Farmer Profits in Batur Village, Getasan District, Semarang Regency - Syarifah, Khariratus; Santosa, Imam; Rifan, Muhammad (STMIK Widya Cipta Dharma, 2024)
The Green Revolution transformed traditional farming systems into conventional farming systems that rely on chemical fertilizers and pesticides, leading to a decline in soil quality. This decline can be addressed by implementing organic farming, which offers benefits such as maintaining and improving soil quality, enhancing product quality, and promoting farmer welfare. In Batur Village, Getasan District, Semarang Regency, there are 35 farmer groups, 5 of which are organic farmer groups managing a total land area of approximately 34.4 hectares. This study aims to evaluate the effects of organic and conventional farming on soil quality and farm profits in Batur Village, with the objective of promoting organic farming practices. The research utilized the composite method for soil sampling and conducted interviews to determine farm profits. Data were analyzed using an independent sample t-test. The results indicate that while soil properties were not significantly different between the two farming systems, organic farming demonstrated higher values for C-organic, N-total, permeability, field capacity, pH, soil consistency, and total soil microbial count compared to conventional farming. Conversely, salinity and porosity values were higher in conventional farming. Additionally, organic farming had lower production costs than conventional farming.